Modeling the distance error and performance analysis in IR-UWB positioning system - MENG Jing1; ZHANG Qin-yu1; ZHANG Nai-tong12; CHEN Ping2; LIU Ning-ning3 (Tongxin xuebao)
The multipath and NLOS distance errors in indoor positioning due to the propagation characteristics of IR-UWB were analyzed,based on the coherent TOA ranging algorithm.Utilized the statistical information of IEEE 802.15.4a channel model,the multipath error was modeled in terms of system bandwidth in both LOS and NLOS envi-ronment.And the NLOS extra distance error was derived in terms of obstacle thickness,transceiver distance and the in-cidence angle as the IR-UWB signal propagated through walls.The positioning performance via triangulation was ana-lyzed as given the prior information of the NLOS distance error in completely NLOS environment.